2015
DOI: 10.1371/journal.pone.0138710
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NF-κB and NF-κB-Regulated Gene Expression by Apigenin through IκBα and IKK Pathway in TRAMP Mice

Abstract: Aberrant Nuclear Factor-κappaB (NF-κB) activation due to rapid IκBα turnover and high basal IκBα kinase (IKK) activity has been frequently observed in prostate cancer. Apigenin, a naturally occurring plant flavone, exhibits anti-proliferative, anti-inflammatory and anti-carcinogenic activities by inhibiting NF-κB pathway, through a mechanism not fully understood. We found that apigenin feeding in microgram doses (bioavailable in humans) inhibited prostate tumorigenesis in TRAMP mice by interfering with NF-κB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 66 publications
2
60
0
1
Order By: Relevance
“…Apigenin administration inhibited prostate tumorigenesis in TRAMP mice and interfered with the NF‐κB‐driven pathway. Apigenin significantly reduced tumor volumes of the prostate in TRAMP mice . Apigenin significantly inhibited tumor growth and blood‐borne metastasis in mice subcutaneously injected with PLC/PRF/5 cells.…”
Section: Regulation Of Nf‐κb Pathwaymentioning
confidence: 97%
“…Apigenin administration inhibited prostate tumorigenesis in TRAMP mice and interfered with the NF‐κB‐driven pathway. Apigenin significantly reduced tumor volumes of the prostate in TRAMP mice . Apigenin significantly inhibited tumor growth and blood‐borne metastasis in mice subcutaneously injected with PLC/PRF/5 cells.…”
Section: Regulation Of Nf‐κb Pathwaymentioning
confidence: 97%
“…Effects of EGCG on the expression of anti-apoptotic proteins. Changes of expression of members of the Bcl-2 family and inhibitor of apoptosis (IAP) family result in chemotherapy resistance of NPC cells [16,17]. NF-κB inhibits apoptosis via its ability to bind to anti-apoptotic genes, and change the expression of anti-apoptis protiens , like Bcl-2, Bcl-XL, and IAPs family [18].…”
Section: Resultsmentioning
confidence: 99%
“…Apigenin has cytostatic and cytotoxic effects on various cancer cells at different doses (Table ), including pancreatic cancer BxPC‐3, PANC‐1, AsPc‐1, Panc‐1, and MiaPaCa‐2 cells (Johnson & de Mejia, ; Wu et al, ); prostate cancer DU145, LNCaP, and PC‐3 cells (Oishi et al, ; Shukla, Fu, & Gupta, ); breast cancer MDA‐MB‐231, MDA‐MB‐453, MBA‐MB‐468, MCF‐7, MCF‐10A, and SK‐BR‐3 cells (Bai, Jin, Yang, Zhu, & Cai, ; Harrison, Coombs, Delaney, & Hoskin, ; Seo et al, ); ovarian cancer SKOV3 cell (Suh, Jo, Lee, & Lee, ); cervical cancer HeLa, CaSki, and C33A cells (Oh et al, ; Zheng, Chiang, & Lin, ); lung cancer H1299, H460, and H2030 cells (Lee et al, ); glioma and glioblastoma C6, U251, and GL‐15 cells (Santos et al, ; Wang et al, ); osteosarcoma U2OS and MG63 cells (Liu et al, ); papillary thyroid carcinoma BCPAP cell (Zhang et al, ); bladder cancer T‐24 cell (Shi, Shiao, Lee, & Shih, ); colorectal cancer cells (Xu et al, ); and leukemia cells (Ruela‐de‐Sousa et al, ). The antitumor effect of apigenin has also been validated in vivo experiments, indicating that it can significantly prolong the survival time and suppress the tumor growth (Chen, Landis‐Piwowar, Chen, & Dou, ; Shukla et al, ).…”
Section: Antitumor Effectmentioning
confidence: 99%
“…The antitumor effect of apigenin may result from a complex interplay. Many data have shown that apigenin may block the phosphorylation and degradation of IκB α by inhibiting IKK activation, which in turn lead to the suppression of nuclear factor (NF)‐κB activation and subsequent downregulation of NF‐κB‐mediated genes involved in the proliferation (cyclin D1 and cyclooxygenase‐2 [COX‐2]), anti‐apoptosis (Bcl‐2 and Bcl‐xL), and angiogenesis (vascular endothelial growth factor [VEGF] of cancer cells) (Johnson & de Mejia, ; Seo et al, ; Shukla et al, ; Wang et al, ; Wu et al, ). Apigenin may also decrease the levels of cyclin A, cyclin B1, cyclin E, CDK2, Cdc2, and Cdc25C to block the cell cycle progression (subG1 phase accumulation), and increase the levels of Bax, Bad, Bak, caspase‐3, caspase‐7, and caspase‐9 to strengthen the caspase‐dependent apoptosis in human bladder cancer T‐24 cell (Shi et al, ).…”
Section: Antitumor Effectmentioning
confidence: 99%